Ethylene suppresses tomato (Solanum lycopersicum) fruit set through modification of gibberellin metabolism. (11th June 2015) - Shinozaki, Yoshihito; Hao, Shuhei; Kojima, Mikiko; Sakakibara, Hitoshi; Ozeki‐Iida, Yuko; Zheng, Yi; Fei, Zhangjun; Zhong, Silin; Giovannoni, James J.; Rose, Jocelyn K.C.; Okabe, Yoshihiro; Heta, Yumi; et al.
Summary Fruit set in angiosperms marks the transition from flowering to fruit production and a commitment to seed dispersal. Studies with Solanum lycopersicum (tomato) fruit have shown that pollination and subsequent fertilization induce the biosynthesis of several hormones, including auxin and gibberellins (GAs), which stimulate fruit set. Circumstantial evidence suggests that the gaseous hormone ethylene may also influence fruit set, but this has yet to be substantiated with molecular or mechanistic data. Here, we examined fruit set at the biochemical and genetic levels, using hormone and inhibitor treatments, and mutants that affect auxin or ethylene signaling. The expression of system–1 ethylene biosynthetic genes and the production of ethylene decreased during pollination‐dependent fruit set in wild‐type tomato and during pollination‐independent fruit set in the auxin hypersensitive mutant iaa9–3. Blocking ethylene perception in emasculated flowers, using either the ethylene‐insensitive Sletr1–1 mutation or 1–methylcyclopropene (1–MCP), resulted in elongated parthenocarpic fruit and increased cell expansion, whereas simultaneous treatment with the GA biosynthesis inhibitor paclobutrazol (PAC) inhibited parthenocarpy. Additionally, the application of the ethylene precursor 1–aminocyclopropane‐1‐carboxylic acid (ACC) to pollinated ovaries reduced fruit set. Furthermore, Sletr1–1 parthenocarpic fruits did not exhibit increased auxin accumulation, but rather had elevated levels of bioactive GAs, most likely reflecting an increase in transcripts encoding the GA‐biosynthetic enzyme SlGA20ox3, as well as a reduction in the levels of transcripts encoding the GA‐inactivating enzymes SlGA2ox4 and SlGA2ox5. Taken together, our results suggest that ethylene plays a role in tomato fruit set by suppressing GA metabolism.